2022
DOI: 10.1111/joss.12775
|View full text |Cite
|
Sign up to set email alerts
|

What are the motives underlying Brazilians' food choices? An analysis of the Food Choice Questionnaire and its relationship with different sample characteristics

Abstract: The first aim of this study was to evaluate the psychometric properties of the Food Choice Questionnaire (FCQ)-using the original model-in a sample of 1480 Brazilian adults (69.5% female). The second aim was to rank the reasons underlying the participants' food choices using average FCQ scores and 95% confidence interval. The third aim was to evaluate the relationship between food choice motives and sample characteristics using multiple logistic regression and odds ratios. The validity, the invariance across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…According to da Silva et al, motives of health, mood, convenience, sensory appeal, natural content, weight control, familiarity, and ethical concern in food choice were higher in females than males. 4 Schliemann et al found that 7 food dimensions as health, mood, convenience, sensory appeal, natural content, price, and weight control were associated with sex, and females had exhibited higher scores than males as our study. 18 In the present study, sensory appeal and weight control scores showed significant differences with respect to gender.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…According to da Silva et al, motives of health, mood, convenience, sensory appeal, natural content, weight control, familiarity, and ethical concern in food choice were higher in females than males. 4 Schliemann et al found that 7 food dimensions as health, mood, convenience, sensory appeal, natural content, price, and weight control were associated with sex, and females had exhibited higher scores than males as our study. 18 In the present study, sensory appeal and weight control scores showed significant differences with respect to gender.…”
Section: Discussionsupporting
confidence: 62%
“…have impacts on food choice decisions. 4,5 Steptoe et al developed a food choice questionnaire (FCQ), consisting of 36 items, testing health-related and nonhealth-related motives of food choice, grouped into 9 dimensions as health, mood, convenience, sensory appeal, natural content, price, weight control, familiarity, and ethical concern. 6 Each dimension includes 3-6 items.…”
mentioning
confidence: 99%
“…The participants completed the Brazilian Portuguese version of the FCQ (Heitor et al, 2015). The FCQ has been used in different contexts (Markovina et al, 2015), with support from Brazilian studies (da Silva et al, 2022;Heitor et al, 2019) that have shown its adequate validity (e.g., Comparative Fit Index and Tucker-Lewis Index >.95, Root Mean Square Error of Approximation <.08, factor loadings >.65, and average variance extracted >.50) and reliability (e.g., test-retest reproducibility >.76; ordinal alpha coefficients >.85). Data Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, consumer research is fundamental in the context of sensory science. Within these methodologies market research is noteworthy to understand consumer behavior in relation to food, as demonstrated in previous studies (Doungtip, Sriwattana, & Kim, 2019;Gama, Adhikari, & Hoisington, 2018;Grymshi, Crespo-Cebada, Elghannam, Mesías, & Díaz-Caro, 2021;Silva, Marôco, Alvarenga, & Campos, 2022;Veiga, Johann, Lima, Kaushik, & Mitterer-Daltoé, 2021).…”
Section: Introductionmentioning
confidence: 99%